Effect of the Changes in Bulk Density and Granulometric Properties on the Strength Properties of the Moulding Sand Mixtures - Hudák, Henrietta; Varga, László (International Journal of Engineering and Management Sciences, 2020)
Foundry technology uses a lot of several natural materials. Sands use for preparing mixtures whereby making moulds or cores. Sand is defined as a granular, refractory major portion of mixture (90 – 98% in dependence on used binder). Sand properties depend on it has chemical and mineralogical composition; mainly particle size distribution and shape of grains and its size and sand surface texture. A comparative measurement of two quartz sand with different surface quality was carried out. Greensand mixtures were prepared to measure their permeability, compressive strength and wet tensile strength. The strength of sand mixtures has two main components. One of them is the cohesion of the binder; the other one is the adhesion between the binder and the foundry sand. The aim of this research is to determine the ratio of cohesion and adhesion within the strength values.